1979
DOI: 10.1111/j.1365-2265.1979.tb01359.x
|View full text |Cite
|
Sign up to set email alerts
|

SUPPRESSION OF PLASMA ACTH CONCENTRATION BY ANGIOTENSIN II INFUSION IN NORMAL HUMANS AND IN a SUBJECT WITH a STEROID 17α‐HYDROXYLASE DEFECT

Abstract: Six healthy subjects were infused with angiotensin II and plasma concentrations of angiotensin, ACTH and cortisol were measured before, during and after the infusion. In all cases the plasma ACTH concentration fell as plasma angiotensin increased and rose again, sometimes to higher than basal levels, when the angiotensin infusion was terminated. These effects were most marked at the highest rate of infusion (8 pmol/kg/min) and, at the lower rates (2 and 4 pmol/kg/min), there was some recovery of ACTH levels du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

1980
1980
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 27 publications
3
12
0
Order By: Relevance
“…In addition, earlier cell-based studies demonstrated that AngII could both stimulate and suppress B production from adrenal cells depending upon the origin of such cells; the stimulatory effect was observed in 'fasciculata-rich' cells and not in total adrenal cells (Spinedi et al 1989). However, a previous small study of human volunteers infused with AngII demonstrated temporary ACTH suppression, which could be in keeping with our results (Semple et al 1979). However, in the latter study, ACTH levels eventually recovered and thus we might have observed a rise in glucocorticoid levels in our subjects if we had extended the sampling time after cessation of infusion.…”
Section: Effect Of Agonists On Corticosteroid Productionsupporting
confidence: 69%
“…In addition, earlier cell-based studies demonstrated that AngII could both stimulate and suppress B production from adrenal cells depending upon the origin of such cells; the stimulatory effect was observed in 'fasciculata-rich' cells and not in total adrenal cells (Spinedi et al 1989). However, a previous small study of human volunteers infused with AngII demonstrated temporary ACTH suppression, which could be in keeping with our results (Semple et al 1979). However, in the latter study, ACTH levels eventually recovered and thus we might have observed a rise in glucocorticoid levels in our subjects if we had extended the sampling time after cessation of infusion.…”
Section: Effect Of Agonists On Corticosteroid Productionsupporting
confidence: 69%
“…Neither explanation seems likely, however, since infusion of ACTH causes a brisk increase in aldosterone, often greater than that obtained in normal subjects. 16 Exogenous All inhibits ACTH in normal subjects. 1 ' In a recent study, 14 infusion of ACTH at a low, constant rate restored the response of aldosterone to simultaneously-infused All in Conn's syndrome.…”
Section: Aldosterone and 18-hydroxycorticosteronementioning
confidence: 99%
“…14 Explanations of this poor response, which is well documented, 16 include the autonomous nature of the tumor secretion and a failure of exogenous All to penetrate the steroid-secreting tissue. Neither explanation seems likely, however, since infusion of ACTH causes a brisk increase in aldosterone, often greater than that obtained in normal subjects.…”
Section: Aldosterone and 18-hydroxycorticosteronementioning
confidence: 99%
“…However, data published thus far do not indicate a direct, causal relationship between AT and cortisol in human models [159] . Data regarding acute effects of AT or angiotensin infusion on HPA axis function are limited, with some studies describing no effect [160,161] , while others report a decrease in ACTH or cortisol secretion [162,163] in humans. Of note, a recent paper by Sanchez-Lemus et al [164] showed that angiotensin II receptor 1A (AT1A) blockade increased basal circulating levels of corticosterone in rats.…”
Section: Angiotensinogen and The Hpa Axismentioning
confidence: 99%